FEM analysis (3D) of reinforced concrete beam with openings - Liang, Kai Jun (2015)
Concrete beam with openings usually use to provide building services, such as conduits and pipes to pass through the beam so that the layout on water reticulation and electrical system will be more systematic. It also provide the ease of maintenance on building utility and reduces the financial during construction of high-rise building. However, beam with opening experience great losses of load capacity. In order to regain such losses, the strengthening method is investigated so that the strength of the concrete beam will be able to cover to the maximum. In this study, the behavior of the openings were investigated in terms of load-deflection, crack pattern and stress distribution. The simulation of strengthening concrete beam with openings by using CFRP laminates were conducted on RC beam with openings. There were three different types of beam that was analyzed in this study, which were solid RC beam, RC beam with openings and the strengthening RC beam with openings by using CFRP laminates. They were modelled using finite element software, ANSYS 12.0 in three degree of freedom. The location of the openings distinguished into zero distance, 140 mm and 280 mm from the supports. The beams were analyzed under four points loading. The result from numerical analysis was compared with the experimental result. The un-strengthened RC beams were found out that the beam reduced the ultimate load capacity at about 67 – 80% of the control beam. When the location of the opening was shifted further away from the support, the beam experienced less reduction of the ultimate load of the solid beam. Thus, the critical location of the opening was concluded at the face of the support. However, whenever the CFRP was installed around the opening region. The beam was able to fortify and regained at about 34 – 44% of ultimate load of the solid beam. Even though the beam was applied with CFRP laminates, they eventually failed on the shear zone. In conclusion, this research was able to prove that the beam was fortified by the CFRP strengthening method. A good agreement between numerical result and experimental result in literature was obtained based on the load-deflection relationship.